FAKTOR-FAKTOR PENGHAMBAT EFEKTIVITAS KERJASAMA PENANGANAN KASUS PENYELUNDUPAN NARKOTIKA ANTARA INDONESIA DAN MALAYSIA (STUDI KASUS: PROVINSI RIAU 2019-2020) - Velysia Elga Pratiwi; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The purpose of this study was to find out why the cooperation between the Indonesian and Malaysian governments in dealing with narcotics smuggling cases in Riau Province was not effective and what were the inhibiting factors for the effectiveness of cooperation between Indonesia and Malaysia in order to minimize narcotics smuggling cases, especially in Riau Province. The number of narcotics smuggling cases in Indonesia has made the government declare Indonesia a narcotics emergency. From year to year narcotics smuggling cases between Indonesia and Malaysia continue to increase so that there are indications that the cooperation between the two countries is not working effectively because these cases keep repeating themselves and increasing.This research is also guided by the theory of International Cooperation and uses qualitative methods. Data collection techniques include interviews and literature studies from several journals, books, documents, and websites. This study shows the ineffectiveness of cooperation and the inhibiting factors experienced by the Indonesian and Malaysian governments in dealing with narcotics smuggling cases. The results of this study conclude that the obstacles or inhibiting factors that make the cooperation between the two countries ineffective are inadequate facilities and infrastructure, the level of quality of the apparatus' activities and the inadequate number of officers, policy conflicts between Indonesia and Malaysia, and weak supervision and prosecution. law. Keywords: Inhibiting Factors, Cooperation, Ineffectiveness, POLRI, PDRM, Narcotics